Four new species of Indasclera Švihla from the Oriental Region (Coleoptera: Oedemeridae) - Poloni, Riccardo (Zootaxa, 2023)
Four new species of Indasclera Švihla, 1980 are described and illustrated: Indasclera bipartita n. sp. from Laos, I. hajeki n. sp. from Malaysia, I. pusilla n. sp. and I. thailandica n. sp., both from Thailand. In addition, a dichotomous key for the I. haemorrhoidalis species group is given.